AN INTEGRATED INFORMATION SYSTEM ON BIORESOURCE COLLECTIONS OF THE FASO OF RUSSIA - S. A. Lashin; D. A. Afonnikov; M. A. Genaev; F. V. Kazantsev; E. G. Komyshev; E. A. Oschepkova; А. V. Petrov; D. A. Rasskazov; A. A. Smirnova; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
Biological collections play a huge role in studying biological diversity as systematic storages of biological materials in all combinations and forms. Collection materials have generally been formed over hundreds of years and may describe a vast number of samples counted by billions. Great efforts are made to preserve these materials, as well as to obtain more and more samples. The Russian Federation occupies a huge land area, has a long coastline and huge natural resources, a variety of natural and ecological zones. In this regard, its territory is unique from the viewpoint of biodiversity and development of biological collections. Currently, a large number of collections are being developed in Russia, but there are a number of problems associated, first of all, with the lack of an integrated information resource on bioresource collections (BRC). In order to support the development of scientific infrastructure, the Federal Agency for Scientific Organizations (FASO of Russia) has been working on the development of unified approaches to the use of existing bioresource collections and the establishment of the integrated information system. The paper presents an information portal designed to provide uniform methods of work for all BRC organizations of the FASO of Russia: input, storage, updating and differentiated access to specific information about storage units and their characteristics. The information system “Bioresource Collections of Scientific Organizations” (IS BRC) has been developed as a Webportal (www.biores.cytogen.ru) integrating databases on bioresource collections of the FASO of Russia and graphical user interface. Access control to the databases integrated into the IS BRC is performed through authorized program access for viewing records, their creation and editing on the basis of REST technology. The graphical user interface (GUI) provides the following features in accordance with the access rights: authorized access to the BRC database; viewing BRC database records; editing BRC database records; creating and deleting BRC database records; statistical data analysis in the BRC database; generation of summary reports on the BRC database; export of records content in PDF/RTF/JSON format. The graphical user interface was implemented using the DRUPAL 7.0 toolkit. Architecturally, the portal is concerned as a central node with a series of modules communicating through the unified interfaces. In this way, we solve the problem of connecting new data sources (collection databases) implemented in different DBMS. Given the fact that currently many organizations support access to the catalogues of their collections independently, the portal also provides external links to these Web resources. At the same time, some information on collections is stored within the BRC databases of the FASO of Russia’s portal in unified formats. The portal contains the following functional sections: the home page containing general information on bioresource collections, the catalog of collections, individual pages for each particular collection with a short description (information about curators, statistical information about the number of storage units in the collection and the number of publications, as well as a link to the catalog of storage units of this BRC). Currently the portal contains more than 13 thousand entities of 65 bioresource collections organizations of the FASO of Russia. It is still being extended.